Fatwas (The Book of Congregational Prayers) From the Book (Fatwas of Jurisprudence) By Ibn Al-Khayyat Al-Qardaghi Study and achieving - Rashad Saeed xidr; Omid Najmaddin Mufti (QALAAI ZANIST JOURNAL, 2023)
It is known that Muslim scholars tried by various means to spread religion and science among nations and cities, after they were firmly established in it, seeking the pleasure of God Almighty and following His Noble Messenger, may God’s prayers and peace be upon him. The Sunnah, and they took various paths in this scientific axis, including the path of answering the questions that were directed to them by the general public or those who were less than them in knowledge, and regarding the calamities and rulings that may arise. The Kurdish scholars in Islamic history were not exempt from other peoples who voluntarily entered Islam in the service and propagation of religion, but they have taken the lead in this regard. Verification of papers from a manuscript book, which is for the great scholar, the scholar Sheikh Abdul Rahman Ibn Al-Khayyat Al-Qardaghi (d. 1335 AH), from (The Book of Congregational Prayers) in the manuscript book (Fatwas Fiqh). Hoping that this effort will continue, and other scientific efforts to highlight the glorious heritage of our scholars, and to publish and disseminate the great services they provided for the sake of science.